Recent Advances of Graphene‐Based Wearable Sensors: Synthesis, Fabrication, Performance, and Application in Smart Device - Fatemeh Saeedi; Reza Ansari; Mojtaba Haghgoo (Advanced Materials Interfaces, 2025)
Abstract In recent years, graphene has emerged as a promising material for flexible wearable sensors due to its exceptional properties, including flexibility, high surface area, excellent conductivity, and remarkable mechanical strength. This review article provides a comprehensive analysis of graphene synthesis techniques, focusing on both traditional methods and advanced laser‐based approaches such as laser reduction, laser ablation, and laser‐induced graphene. Additionally, various laser fabrication technologies, surface modification strategies are discussed to enhance graphene's physical and chemical properties and heteroatom doping. The article further explores the diverse applications of graphene in wearable sensors, encompassing mechanical sensors, electrophysiological sensors, and gas and humidity sensors. By examining the advancements in fabrication techniques and sensor applications, this study highlights the potential of graphene‐based sensors to improve the performance and predictability of wearable devices significantly.